2006
DOI: 10.1016/j.mssp.2006.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Non-collinear magnetic states of Mn5Ge3 compound

Abstract: Mn 5 Ge 3 thin films epitaxially grown on Ge(111) exhibit metallic conductivity and strong ferromagnetism up to about 300 K. Recent experiments suggest a non-collinear spin structure. In order to gain deep insights into the magnetic structure of this compound, we have performed fully unconstrained ab-initio pseudopotential calculations within density functional theory, investigating the different magnetic states corresponding to Collinear (C) and Non-Collinear (NC) spin configurations. We focus on their relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Similar T C enhancement (350 K) has been reported on strained Mn 5 Ge 3 thin films on GaAs(001) substrate . Also, it has been theoretically calculated that an increase on the cell volume produces a non‐collinear alignment of the magnetic moment of the Mn atoms, together with a high spin configuration . As expected, the increase on the volume of the Mn 5 Ge 3 cell on the nanoislands should be accompanied by a higher thermal stability of the Mn magnetic moments.…”
Section: Resultssupporting
confidence: 79%
“…Similar T C enhancement (350 K) has been reported on strained Mn 5 Ge 3 thin films on GaAs(001) substrate . Also, it has been theoretically calculated that an increase on the cell volume produces a non‐collinear alignment of the magnetic moment of the Mn atoms, together with a high spin configuration . As expected, the increase on the volume of the Mn 5 Ge 3 cell on the nanoislands should be accompanied by a higher thermal stability of the Mn magnetic moments.…”
Section: Resultssupporting
confidence: 79%
“…The calculated total spin moment per Mn atom is 2.75 µ B , in agreement with previous calculations. 34,41,49,50 This value is slightly higher than the experimental one, i.e. 2.60 µ B .…”
Section: B Ge3mn5 a Test Materialsmentioning
confidence: 56%
“…Polarized neutron diffraction studies on the spatial distribution of the magnetization density in Mn 5 Ge 3 revealed two crystallographically nonequivalent Mn sublattices, namely, Mn I and Mn II , with two distinctive magnetic moments of 1.96 μ B and 3.23 μ B , respectively . Density function calculations also suggested the coexistence of two energetically degenerate ferromagnetic states, collinear and noncollinear configurations, in the Mn 5 Ge 3 lattice, and the observed cusp in the d R /d T curves may be attributed to a possible magnetic transition between these two states. A similar scenario occurs in the antiferromagnetic Mn 5 Si 3 that has the same crystal structure as Mn 5 Ge 3 .…”
Section: Resultsmentioning
confidence: 89%